Classical arabic: a critique of thumadir bint amr’s (al-khansa) poetry (2019)
Classical Arabic is taught in several institutions across the globe especially at the University level where Arabic is a course of study, besides studies of individual scholars and translations of their literary writing. The study is highly concentrated on both poetry and prose written by Arab male writers of classical period. The works ofpoetess in classical Arabic literature have been largely neglected especially that oj Al-Khansa. Scholars and critics fail to realize the extent of their achievements and their abilities to face comparison with other poets in both classical and modern Arabic literature. This paper therefore, explores the balance and provides a conspectus of Thumadir bint Amr popularly known as Al-Khansa’s poetical composition in a such a form as may prove helpful not only to Arabic scholars, but also to inform th readers of Arabic literature. Here in this paper, the expression classica poetry is taken to mean the poetry before the advent of Islam in Arabia!. Peninsula. This paper also introduces classical Arabic poetry preoccupation with people, whether individuals or groups, that is, tribe, party, sect or race. The life and works of selected poetess is also exhibited in the paper with analysis of the work in a classical form. The paper posits that the classical Arabic poetry composed by Thumadir bint Amrhad showcased thy significance of women in literary circle of the period.